Bipolar Pythagorean Neutrosophic Aggregation Operator for Voice of the Guest: Evaluating Hotel Management Service Quality through Customer Feedback - Ying Zhong; Yanyan Yao; Xiaoting Huang (Neutrosophic Sets and Systems)
Providing top-notch service is crucial to preserving customer loyalty and happiness in the cutthroat hospitality sector of today. The "Voice of the Guest" is emphasized as a crucial data source in this study, which examines how hotel management service quality is assessed from the viewpoint of consumer input. The research highlights key service aspects, such as personnel professionalism, cleanliness, responsiveness, and service diversity, by combining qualitative and quantitative analysis. Eight hotel options were evaluated. This study uses the Bipolar Pythagorean Neutrosophic Number to evaluate the criteria and alternatives. The neutrosophic aggregation operator is used to combine values in criteria and alternatives. The results show notable differences in how guests perceive various hotel types, underscoring the impact of location, automation, and personalized services on quality assessment. The study emphasizes how crucial it is for hotel operations to actively use customer feedback systems, including surveys, reviews, and sentiment analysis tools, as a real-time quality control tool. This data-driven method supports guest-centered management techniques and ongoing service enhancement.